1981
DOI: 10.1007/bf02318912
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of coniferin β-glucosidase to lignification in various plant cell suspension cultures

Abstract: A combination of the phytohormones naphthalene acetic acid and benzylaminopurine (5gM each) allows Lignification in various plant cell cultures. This system has been used to investigate the relationship between the coniferin-hydrolyzing 13-glucosidase activity and lignification. In Petroselinum hortense and Triticum aestivum cell cultures the appearance of this enzymatic activity coincided with lignification. In parsley cell cultures it was moreover shown that this activity appears concomitantly with other lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…P-Glucosidases capable of hydrolyzing coniferin have been detected in suspension culture systems (Hosel and Todenhagen, 1980;Hosel et al, 1982) and seedlings (Marcinowski and Grisebach, 1978), but, to our knowledge, a coniferin glucosidase has not been idektified that derives from differentiating xylem of mature trees, the most active site for lignin biosynthesis in woody plants.…”
mentioning
confidence: 97%
“…P-Glucosidases capable of hydrolyzing coniferin have been detected in suspension culture systems (Hosel and Todenhagen, 1980;Hosel et al, 1982) and seedlings (Marcinowski and Grisebach, 1978), but, to our knowledge, a coniferin glucosidase has not been idektified that derives from differentiating xylem of mature trees, the most active site for lignin biosynthesis in woody plants.…”
mentioning
confidence: 97%
“…In soybean (Glycine max), a b-glucosidase in vitro specific for coniferin, syringin, and ferulic acid 4-O-b-D-glucoside has been isolated (Hosel and Todenhagen, 1980). In cell suspension cultures of Petroselinum hortense and wheat (Triticum aestivum), the appearance of b-glucosidase activity is correlated with the initiation of lignification and, sometimes, with the appearance of other enzymes involved in lignin biosynthesis (Hosel et al, 1982).…”
mentioning
confidence: 99%
“…Some authors suggested that the rate and the location of lignification are controlled by these β-glucosidases. 184 However, it is still unclear whether coniferin and other glucosylated monolignols are obligate precursors of lignin. In 1933, Erdtman 185 proposed that monolignols are polymerized into lignin by an oxidative mechanism involving free-radical intermediates.…”
Section: Generalities and Biosynthesismentioning
confidence: 99%